Volatile Organic Compound Emissions from Indoor Fragrance Diffusers - Wen-Hsi Cheng; Yi-Chian Chen; Song-You Shih (Atmosphere, 2023)
People today spend most of their time indoors; many use fragrances in closed restrooms and bathrooms at home and in public spaces for masking odors. However, volatile organic compounds (VOCs) that are emitted from indoor fragrances have been reported in recent years to pose a risk to health. In this work, microneedle trap samplers (NTSs) were fabricated, packed with sulfonated divinylbenzene (SDVB) adsorbents, and used in passive mode to extract the VOCs that were emitted by bamboo diffusers in fragrance bottles in bathrooms. Instrumental analysis revealed that the main VOCs that were emitted from chemically synthesized fragrances were ethanol (19.2–40.5 ppb), propylene glycol (273.4–527.9 ppb), and 3-ethylbenzaldehyde (3.8–12.4 ppb). Lower indoor air change rates were associated with significantly higher emitted concentrations of VOCs. 3-Ethylbenzaldehyde is a strong respiratory irritant, and outdoor pollutants such as toluene, which escapes from paints, have a negative impact on indoor air quality.